Blue laser welding of 7075-T6 aluminum alloy and carbon fiber reinforced polyetheretherketone. (November 2022) - Yuan, Guixin; Zhou, Zhukun; Li, Xiang; Long, Yu
Highlights: Using 7075-T6 aluminum alloy and carbon fiber reinforced polyetheretherketone as research materials, the welding effect of blue laser and fiber laser oscillation welding was compared and discussed. Due to the easy absorption characteristics of the blue laser wavelength, the obtained welded joint has fewer defects and twice the joint strength compared with fiber laser oscillation welding. The resin embedded in the molten pool causes columnar crystals to grow around the resin, especially in fiber laser oscillation welding. The established finite element model is in good agreement with the test results, and can effectively guide and predict the test results. Abstract: Laser welding was employed to join aluminum alloys and carbon fiber reinforced polymers (CFRP) inexpensively and quickly in lightweight automobiles, especially in the field of new energy vehicles. In recent years, a new way to obtain stronger high-reflection alloy laser welded joints is blue laser welding (BLW). An innovative comparative experiment was conducted between blue laser welding (BLW) and fiber laser oscillation welding (FLOW), using 7075-T6 aluminum alloy and carbon fiber reinforced polyetheretherketone (CFRP-PEEK) as study materials, and the laser welding mechanism is explained. It was concluded that the maximum tensile force of the BLW joint was 478 N, which is higher than the 290 N tensile force of FLOW. In addition, the maximum residual stress in the BLW joint is 325 MPa, which is lower than that of FLOW. The mechanism affecting the strength of the joint is the presence of a larger number and size of bubble defects inside the FLOW melt pool, and the presence of a demarcation line between the columnar and equiaxed crystals around these bubble defects is observed. This boundary line means that there is a large temperature difference. Combined with the finite element simulation results, the existence of the temperature difference leads to a different solidification sequence around the bubble defect inside the molten pool, so stress concentration occurs. Therefore, the interface of the FLOW joint is not tightly combined, and a gap phenomenon occurs. Furthermore, when the laser power increases, PEEK resin is extruded into the melt pool as the melt pool size approaches that of the aluminum alloy, as observed in the BLW joint. The same demarcation line between columnar and equiaxed crystals structure was observed in the PEEK resin, so that the stress concentration around the PEEK resin can lead to weakened joints in high power welding.